TANTANGAN KORUPSI, OLIGARKI, DAN POLITIK UANG: ANTARA KEKUASAAN DAN KEPENTINGAN - Umar Iskandar; Muh. Ersyad Indra Praja; Darniaty Asis (Journal of Innovation Research and Knowledge, 2025)
This study examines the interrelation between corruption, oligarchy, and money politics as a multidimensional challenge within Indonesia’s political system. Corruption is understood not merely as individual misconduct, but as a structural phenomenon rooted in power configurations and unequal distribution of resources. Political–economic oligarchy reinforces corrupt practices through the concentration of power in the hands of a small elite, while money politics operates as a patronage mechanism that preserves their dominance in electoral processes. This research employs a qualitative approach using library research on books, journal articles, international organization reports, and policy documents. The data are analyzed through content analysis and thematic analysis to map the patterns linking oligarchic power structures, money politics, and the digitalization of governance. The findings indicate that digital governance through e-governance, the use of big data and artificial intelligence, as well as the strengthening of public participation and anti-corruption education, has the potential to form an integrative and sustainable model for preventing and combating corruption. The synergy of technological innovation, institutional reform, and civic engagement is crucial to breaking the cycle of corruption–oligarchy–money politics and reinforcing a transparent and accountable democracy in Indonesia